Pengaruh Faktor Ekonomi dan Moneter terhadap Bank Konvensional dan Syariah Tahun 2002-2016 - Nurul Huda; Hulmansyah Hulmansyah; Zulihar Zulihar (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to examine the effect of national income (real GDP), inflation rate and money supply previous year (M) t-1 to the amount of money circulating in the current year (M) t and the amount of credit / financing in the current year (Cr ) t both from the activities of Syariah banking and conventional banking. The data was used by publication of Bank Indonesia, the Financial Services Authority and the Central Bureau of Statistics. The analysis data was used multiple linear regression with logarithm approach. Research Result find for conventional bank only variable inflation significantly affect in the money supply (M1), while for Syariah bank in GDP and inflation as well as M1 (ISL) / P) t-1. As for conventional M2 for inflation and GDP was significant. For Syariah banking only GDP was not significant. The Factors were affecting credit conventional bank only inflation only. While Syariah bank all variables were significant.